The prognostic value of an age-adjusted BIG score in adult patients with traumatic brain injury - Bai, Xue; Wang, Ruoran; Zhang, Cuomaoji; Wen, Dingke; Ma, Lu; He, Min (Frontiers in Neurology, 2023)
The base deficit, international normalized ratio, and Glasgow Coma Scale (BIG) score was previously developed to predict outcome of pediatric trauma patients. We designed this study to explore and improve the prognostic value of BIG score in adult traumatic brain injury (TBI) patients. Methods Adult patients diagnosed with TBI in a public critical care database were included in this observational study. BIG score was calculated based on GCS (Glasgow Coma Scale), INR (International Normalized Ratio) and base deficit. Logistic regression analysis was performed to confirm the association between BIG score and outcome of included patients. Receiver operating characteristic (ROC) curves was drawn to evaluate the prognostic value of BIG score and novel constructed models.1034 TBI patients were included in this study with mortality of 22.8%. Non-survivors had higher BIG score than survivors (p<0.001). Results of multivariable logistic regression analysis showed age (p<0.001), pulse oxygen saturation (SpO2) (p=0.032), glucose (p=0.015), hemoglobin (p=0.047), BIG score (p<0.001), subarachnoid hemorrhage (p=0.013) and intracerebral hematoma (p=0.001) were associated with in-hospital mortality of included patients. The AUC (area under the ROC curves) of BIG was 0.669, which was not as high as in previous pediatric trauma cohorts. However, combining BIG with age increase the AUC into 0.764. And the prognostic model composed of significant factors including BIG had the highest AUC of 0.786.Age adjusted BIG score is superior to original BIG in predicting mortality of adult TBI patients.Prognostic model incorporating BIG is beneficial for clinicians to make early triage and treatment decisions in adult TBI patients.